Paleohistological Analysis of “Terror Birds” (Phorusrhacidae, Brontornithidae): Paleobiological Inferences - Jordi Alexis Garcia Marsà; Federico L. Agnolín; Delphine Angst; Eric Buffetaut (Diversity)
Extinct flightless birds of the clades Phorusrhacidae and Brontornithidae are among the most characteristic elements of the South American Cenozoic faunas. Although the anatomy, systematics, paleoecology, and distribution of these birds have been analyzed in some detail, there is not a single work dealing with the osteohistology of these taxa. Herein, we present for the first time paleohistological data for phorusrhacids (Patagornis marshi) and brontornithids (Brontornis burmeisteri). A dense vascularized fibrolamellar matrix and an uninterrupted cortex lacking growth lines indicate similar metabolism and physiological attributes occurring in most extant birds, and they differ from the condition of insular taxa or species living in very stable habitats. This is congruent with recent analyses indicating that phorusrhacids were very active birds lacking insularity-related attributes. It also supports recent growing evidence indicating that these birds’ extinction may be related to climatic and environmental changes rather than being the result of competitive displacement by immigrant placental mammals.